Quantitative differences in neuronal subpopulations between mouse and human dorsal root ganglia demonstrated with RNAscope in situ hybridization. Issue 10 (October 2020) - Shiers, Stephanie; Klein, Rebecca M.; Price, Theodore J.
Abstract : Abstract: Next-generation transcriptomics in combination with imaging-based approaches have emerged as powerful tools for the characterization of dorsal root ganglion (DRG) neuronal subpopulations. The mouse DRG has been well characterized by many independently conducted studies with convergent findings, but few studies have directly compared expression of population markers between mouse and human. This is important because of our increasing reliance on the mouse as a preclinical model for translational studies. Although calcitonin gene-related peptide (CGRP) and P2X purinergic ion channel type 3 receptor (P2X3R) have been used to define peptidergic and nonpeptidergic nociceptor subpopulations, respectively, in mouse DRG, these populations may be different in other species. To directly test this, as well as a host of other markers, we used multiplex RNAscope in situ hybridization to elucidate the distribution of a multitude of unique and classic neuronal mRNAs in peptidergic (CGRP-expressing) and nonpeptidergic (P2X3R-expressing) nociceptor subpopulations in mouse and human DRG. We found a large overlapping CGRP and P2X3R neuronal subpopulation in human, lumbar DRG that was not present in mouse. We also found differential expression in a variety of mRNAs for transient receptor potential channels, cholinergic receptors, potassium channels, sodium channels, and other markers/targets. These data offer insights into the spatial and functional organization of neuronal cell subpopulations in the rodent and human DRG and support the idea that sensory system organizational principles are likely different between both species. Abstract : Supplemental Digital Content is Available in the Text.We provide insight into the organization of nociceptor subpopulations in mice and humans concluding that basic aspects are divergent between species.